1993
DOI: 10.1128/jb.175.24.7808-7818.1993
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure and chemical composition of the sheath of Leptothrix discophora SP-6

Abstract: Light microscopy and transmission electron microscopy of thin sections and metal-shadowed specimens showed that the sheath of Leptothrix discophora SP-6 (ATCC 51168) is a tube-like extracellular polymeric structure consisting of a condensed fabric of 6.5-nm-diameter fibrils underlying a more diffuse outer capsular layer. In thin sections, outer membrane bridges seen to contact the inner sheath layer suggested that the sheath fabric was attached to the outer layer of the gram-negative cell wall. The capsular po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
103
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(111 citation statements)
references
References 41 publications
(41 reference statements)
7
103
0
1
Order By: Relevance
“…Leptothrix species deposit copious amounts of iron hydroxide-encrusted sheaths in the environment where they grow [4]. Chemically active saccharic and proteinaceous groups in the secretions of bacteria are thought to play a key role in binding aqueous inorganic ions [4,9,11,12,[34][35][36][37]. Although Hashimoto et al [18] found a variety of chemical bonds such as Fe-O, Fe-O-Si, Fe-O-P and so on in Leptothrix sheaths, it is still unknown how these chemical bonds are formed in the sheaths: are the iron hydroxides and oxides formed first, then other ions bind to them or vice versa?…”
Section: Ed/xrd-results and Crystallinity Of Sheathsmentioning
confidence: 99%
“…Leptothrix species deposit copious amounts of iron hydroxide-encrusted sheaths in the environment where they grow [4]. Chemically active saccharic and proteinaceous groups in the secretions of bacteria are thought to play a key role in binding aqueous inorganic ions [4,9,11,12,[34][35][36][37]. Although Hashimoto et al [18] found a variety of chemical bonds such as Fe-O, Fe-O-Si, Fe-O-P and so on in Leptothrix sheaths, it is still unknown how these chemical bonds are formed in the sheaths: are the iron hydroxides and oxides formed first, then other ions bind to them or vice versa?…”
Section: Ed/xrd-results and Crystallinity Of Sheathsmentioning
confidence: 99%
“…Indeed, the sheath material of Leptothrix contains organics such as polysaccharides, proteins, and lipids whose active groups are expected to play critical roles to bind aqueous-phase cations [3,6,18,19]. Chan et al [4] showed a strong correlation between the presence of acidic polysaccharides with carboxyl functional groups to the distribution of iron oxyhydroxides in Leptothrix sheath and Gallionella stalks.…”
Section: Introductionmentioning
confidence: 99%
“…In a separate SEM-EDX observation, these particles were shown to contain Fe, O, P and Si as major elements, suggesting that they could aggregate via autooxidation of aquatic-phase elements and/or unidentified chemical bonds (Appendix Figure A1). When specimens cultured in SGPI broth for 3 days were observed with TEM, some sheaths, characterized by a thin or electron-dense thick wall, enclosed bacterial cells ( Figure 4A, arrows), while other sheaths contained degenerated and deformed cell remnants ( Figure 4A, dotted arrows), as reported for cultured L. discophora SP-6 by Emerson and Ghiorse [7]. As illustrated in a longitudinal section of a sheath ( Figure 4B), a body that maintained the shape of a cell (arrow) occasionally coexisted side-by-side with cell remnants (dotted arrow) within a sheath.…”
Section: Resultsmentioning
confidence: 77%
“…The formation of a sheath that contains bacterial cells and extracellular metal-oxidizing activities are the two major phenotypic criteria that distinguish Leptothrix species from closely related bacteria [1,7]. Although the presence of a sheath is thought to confer nutritional and ecological advantages to species of Sphaerotilus and Leptothrix and enables the bacterial cells to attach themselves to solid surfaces and protects them against parasites and predators [1,3], sufficient evidence to explain the significance of the sheath in these bacteria is still lacking.…”
Section: Introductionmentioning
confidence: 99%